Urban environments in Africa : a critical analysis of environmental politics - Myers, Garth Andrew (Bristol : Policy Press, 2017)
Africa's urban population is growing rapidly, raising numerous environmental concerns. Urban areas are often linked to poverty as well as power and wealth, and hazardous and unhealthy environments as the pace of change stretches local resources. Yet there are a wide range of perspectives and possibilities for political analysis of these rapidly changing environments. Written by a widely respected author, this work will mark a major new step forward in the study of Africa's urban environments. Using innovative research including fieldwork data, map analysis, place-name study, interviewing and fiction, the work explores environmentalism from a variety of perspectives, acknowledging the clash between Western planning mind-sets pursuing the goal of sustainable development, and the lived realities of residents of often poor, informal settlements.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 13, 2016).
Keywords: Urban ecology (Sociology) -- Africa; Environmental policy -- Africa; Urbanization -- Environmental aspects -- Africa; Society